Evaluation of decadal shoreline changes in the coastal region of Miri, Sarawak, Malaysia - Anandkumar, A.; Vijith, H.; Ramasamy, Nagarajan; Jonathan, M.P. (2018)
The coastal region of Miri City, Malaysia, in recent years has been excessively occupied by urbanization related to industrial development. The stress and changes in the climatic conditions in the region have induced changes in the shoreline over the last five decades. In this study, the landuse/landcover changes along with spatial and temporal characteristics of the shoreline have been studied for a 74 km coastal belt adjacent to Miri for a period covering 51 years, using geographical information systems (GIS). The landuse/landcover changes between the periods of 1968-2014 are identified and discussed in comparison with the spatial and temporal changes of shorelines in the study area. The results of the landuse/landcover change analysis have highlighted the massive conversion of primary forests as secondary forests, palm oil plantations, and urban areas over the last five decades. Shoreline change detection over the different time periods shows a decade of cyclic reversal of erosion and accretion along the shoreline of Miri. The major accretion spots and erosion hotspots are demarcated and the factors involved in this phenomenon are also identified. The increased sediment delivery through the rivers (the Baram, Miri, and Sibuti rivers) from the upper river catchment region and reclamation activities caused the accretion whereas the erosion hotspots are the results of unscientific development and coastal protection activities.